2020
DOI: 10.2147/opth.s270006
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of Coronavirus in the Conjunctival Tears and Secretions in Patients with SARS-CoV-2 Infection in Sohag Province, Egypt</p>

Abstract: Purpose To assess SARS-CoV-2 virus in conjunctival tears and secretions of positive confirmed COVID-19 patients. Methods A case series study that included 28 positive COVID-19 patients confirmed with nasopharyngeal swab in the period 18–28 May 2020 at Sohag Tropical Medicine Hospital. Tears and conjunctival secretions of these confirmed positive cases were collected with disposable sampling swabs at interval of 3 days after admission due to respiratory symptoms. They we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…The study reported that COVID-19 was found in the secretions of 28.57% of the patients, whereas the majority showed negative results. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The study reported that COVID-19 was found in the secretions of 28.57% of the patients, whereas the majority showed negative results. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, conjunctival swabs were collected within three days from the onset of respiratory symptoms to ensure the presence of higher viral load levels to be detected by (RT-PCR) [ 25 , 26 ]. Conjunctival swabs were taken from the inferior conjunctival sac through eversion of the lower eyelids by sterile cotton tips to explore the lower fornixes of the eye [ 27 ] without topical anesthesia. Tips of the sterile sticks were placed into liquid Virocult ® medium.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] Many studies have evaluated SARS-CoV-2 shedding in conjunctival tears and secretions. 6,7 The presence of viral RNA was confirmed by many studies suggesting its transmission through the eyes. This could explain deaths amongst ophthalmologists and support the importance of safety measures when dealing with symptomatic and asymptomatic patients.…”
Section: Introductionmentioning
confidence: 92%